2019
DOI: 10.3390/nano9081134
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Electrochemical Performance of SbTe Bimetallic Anodes for High-Performance Sodium-Ion Batteries: Roles of the Binder and Carbon Support Matrix

Abstract: Synergism between the alloy materials and the carbon support matrix, in conjunction with the binder and electrolyte additives, is of utmost importance when developing sodium-ion batteries as viable replacements for lithium-ion batteries. In this study, we demonstrate the importance of the binder and carbon support matrix in enhancing the stabilities, cyclabilities, and capacity retentions of bimetallic anodes in sodium-ion batteries. SbTe electrodes containing 20%, 30%, and 40% carbon were fabricated with poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Another chalcogenide material, tellurides (such as SnTe, Sb 2 Te 3 , Bi 2 Te 3 ), with higher conductivity, larger interplanar spacing and higher density compared with oxides, sulfides and selenides, have been widely adopted for SIBs anodes. These intrinsic features allow outstanding rate ability and high theoretical volumetric capacity. , It was revealed that the reaction products between Na-ion and Sb 2 Te 3 were Na 3 Sb and Na 2 Te . Later, the sodiation-desodiation process of Bi 2 Te 3 anode was investigated via in situ XRD and ex situ HRTEM techniques .…”
Section: Conversion-alloying Anode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another chalcogenide material, tellurides (such as SnTe, Sb 2 Te 3 , Bi 2 Te 3 ), with higher conductivity, larger interplanar spacing and higher density compared with oxides, sulfides and selenides, have been widely adopted for SIBs anodes. These intrinsic features allow outstanding rate ability and high theoretical volumetric capacity. , It was revealed that the reaction products between Na-ion and Sb 2 Te 3 were Na 3 Sb and Na 2 Te . Later, the sodiation-desodiation process of Bi 2 Te 3 anode was investigated via in situ XRD and ex situ HRTEM techniques .…”
Section: Conversion-alloying Anode Materialsmentioning
confidence: 99%
“…252−255 These intrinsic features allow outstanding rate ability and high theoretical volumetric capacity. 256,257 It was revealed that the reaction products between Na-ion and Sb 2 Te 3 were Na 3 Sb and Na 2 Te. 258 Later, the sodiationdesodiation process of Bi 2 Te 3 anode was investigated via in situ XRD and ex situ HRTEM techniques.…”
Section: Conversion-alloying Anode Materialsmentioning
confidence: 99%
“…[ 215 ] A comparative study on different binders with electrolyte additive effects on bimetallic SbTe anode in SIB is recently published. [ 216 ] The electrode with the PVDF binders with FEC (5%) as an additive to the electrolytes and containing (20, 30, and 40)% carbon were outperformed by the PAA binder with identical additive. The PVDF cell showed reversible capacities increment with the increase in carbon contents as (34, 69, and 168) mAh g −1 , with a retention of (8.1, 17.4, and 44.8)%, respectively, after 100 cycles.…”
Section: Electrolytesmentioning
confidence: 99%
“…However, DFT calculations predict that Na 3 Sb is prone to being an insulator [25]. (The electronic conductivity of the anode could be activated, for example, by using carbon matrices [26]). Na 3 Bi, on the other hand, is a three-dimensional (3D) nontrivial Dirac semimetal [27], and a number of recent studies discuss Na 3 Bi as an anode material in sodium-ion batteries [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%